2017
DOI: 10.1111/bjdp.12222
|View full text |Cite
|
Sign up to set email alerts
|

Family and individual variables associated with young Filipino children's numeracy interest and competence

Abstract: Children's early numeracy outcomes set the foundation for mathematics learning in their future school years. This study examined how different family and individual variables were associated with the numeracy interest and competence of disadvantaged young children in the Philippines. The numeracy and literacy skills of 673 children living in low-middle income communities were tested. Their parents were also asked to complete a questionnaire on demographics, their home numeracy practices, attitudes about numera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 37 publications
3
29
0
1
Order By: Relevance
“…Overall, only four studies (Zhou et al, 2006 ; Missall et al, 2015 ; Cheung et al, 2018 ; Leyva et al, 2019 ) did not observe any relationship between home numeracy (both questionnaire and observations) and mathematical skills (both comprehensive and specific mathematical measures). In addition, one study showed that the relationship between formal home numeracy and composite mathematical score was negative (Ciping et al, 2015 ).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Overall, only four studies (Zhou et al, 2006 ; Missall et al, 2015 ; Cheung et al, 2018 ; Leyva et al, 2019 ) did not observe any relationship between home numeracy (both questionnaire and observations) and mathematical skills (both comprehensive and specific mathematical measures). In addition, one study showed that the relationship between formal home numeracy and composite mathematical score was negative (Ciping et al, 2015 ).…”
Section: Discussionmentioning
confidence: 95%
“…Two studies with participants from middle- to high-SES families showed that formal numeracy activities were positively associated with children's ( M age = 6 years) composite mathematical score (i.e., Utrecht Early Numeracy Test-Revised) above and beyond children's cognitive skills, linguistic skills, and their home literacy environment (Kleemans et al, 2012 ; Segers et al, 2015 ). However, one study with participants from low- to middle-SES families reported that children's ( M age = 4.3 years) composite mathematical scores were not associated with formal home numeracy activities, but positively related with SES (Cheung et al, 2018 ). Next to these cross-sectional designs, several studies used a longitudinal approach.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Results presented in the current study represent data from Time 5 of a larger longitudinal study (Cheung, Yang, Dulay, & McBride, 2017;Dulay et al, 2018aDulay et al, , 2019. This included a 12-week intervention program for numeracy, dialogic reading, and early literacy skills, with an untrained control group, between Time 1 and Time 2.…”
Section: Analysis Of Clustering Effectsmentioning
confidence: 99%